2008
DOI: 10.1159/000174855
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Utility of Impedance Cardiography Measurements in Elderly Hemodialysis Patients with Coronary Artery Disease

Abstract: Aim: We evaluated the utility of impedance cardiography (IC) in elderly hemodialysis (HD) patients with coronary artery disease (CAD). Patients and Methods: Seventy-five HD patients (30 with CAD) participated. IC cardiac output (ICCO), systemic vascular resistance and pulse pressure (PP) were calculated at baseline, and 30 and 180 days after study entry. ICCO was compared to echocardiography cardiac output (ECO). Relationships of IC measurements and cardiovascular mortality were assessed. Patients were followe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 80 publications
(82 reference statements)
0
2
0
Order By: Relevance
“…Karakitsos et al [24] performed a prospective observational study among 75 HD patients in whom measurements were taken on a midweek morning of a non-dialysis day. The research showed that the CO obtained by ICG (BioZ System) (mean 4.4 ± 1 L) and the CO measured by echocardiography (4.3 ± 0.9 L) were strongly correlated (r = 0.94; p < 0.001).…”
Section: Cardiovascular Emergencies In Dialysis Patientsmentioning
confidence: 99%
“…Karakitsos et al [24] performed a prospective observational study among 75 HD patients in whom measurements were taken on a midweek morning of a non-dialysis day. The research showed that the CO obtained by ICG (BioZ System) (mean 4.4 ± 1 L) and the CO measured by echocardiography (4.3 ± 0.9 L) were strongly correlated (r = 0.94; p < 0.001).…”
Section: Cardiovascular Emergencies In Dialysis Patientsmentioning
confidence: 99%
“…In another study, impedance cardiography was used to assess patients' fluid status during dialysis, using thoracic fluid content and cardiac output [12]. Karakitsos et al compared impedance cardiography with echocardiography in hemodialysis patients [13]. They showed that impedance cardiography can estimate hemodynamics in hemodialysis patients with coronary artery disease and help predict outcome in certain patients.…”
Section: Introductionmentioning
confidence: 99%